Regulating the Solvation Shell Structure of Lithium Ions for Smooth Li Metal Deposition in Quasi‐Solid‐State Batteries. Issue 7 (23rd February 2023) - Zhu, Jiaming; Kang, Cong; Mo, Shengkai; Zhang, Yan; Xiao, Xiangjun; Kong, Fanpeng; Yin, Geping
Abstract: Gel polymer electrolytes (GPE) are promising next‐generation electrolytes for high‐energy batteries, combining the multiple advantages of liquid and all‐solid‐state electrolytes. Herein, we a synthesized GPE using poly(ethylene glycol)acrylate (PEGDA) in order to understand how the GPE efficiently inhibits lithium dendrite formation and growth. The effects of PEGDA on the solvation shell structure of the lithium ion are investigated using density functional theory (DFT) and ab initio molecular dynamics (AIMD) simulations, which are also supported by Raman spectroscopy. The GPE electrolytes with optimal PEGDA concentration exhibit high transference numbers ( t Li + ${{_{{\rm Li}{^{+}}}}}$ =0.72) and ionic conductivity ( σ =3.24 mS cm −1 ). A symmetric lithium ion battery using GPE can be stably cycled for 1200 h in comparison to 320 h in a liquid electrolyte (LE), possibly owing to the high content of LiF (17.9 %) in the solid–electrolyte interphase film of the GPE cell. The observed concentration/electric field gradient observed through the finite element method also accounts for the good cycling performance. In addition, a LiCoO2 |GPE|Li cell demonstrates excellent capacity retention of 87.09 % for 200 cycles; this approach could present promising guidelines for the design of high‐energy lithium batteries. Abstract : Gel to the limit : A gel polymer electrolyte (GPE) is synthesized in situ in the assembled cell using a liquid electrolyte and poly(ethylene glycol)acrylate (PEGDA). This cell is used to understand how the GPE inhibits lithium dendrite formation and growth. A LiCoO2 |GPE|Li cell demonstrates excellent cycling stability, which makes the suggested GPE a promising candidate for use in Li‐ion batteries with high specific energies.